Photoswitchable peptides for spatiotemporal control of biological functions. Issue 69 (14th August 2019) - Albert, Lea; Vázquez, Olalla
Abstract : Bioactive photoswitchable peptides as excellent optochemical tools for cellular processes. Abstract : Light is unsurpassed in its ability to modulate biological interactions. Since their discovery, chemists have been fascinated by photosensitive molecules capable of switching between isomeric forms, known as photoswitches. Photoswitchable peptides have been recognized for many years; however, their functional implementation in biological systems has only recently been achieved. Peptides are now acknowledged as excellent protein–protein interaction modulators and have been important in the emergence of photopharmacology. In this review, we briefly explain the different classes of photoswitches and summarize structural studies when they are incorporated into peptides. Importantly, we provide a detailed overview of the rapidly increasing number of examples, where biological modulation is driven by the structural changes. Furthermore, we discuss some of the remaining challenges faced in this field. These exciting proof-of-principle studies highlight the tremendous potential of photocontrollable peptides as optochemical tools for chemical biology and biomedicine.